Incorporation of GM-CSF or CD40L Enhances the Immunogenicity of Hantaan Virus-Like Particles - Cheng, Lin-Feng; Wang, Fang; Zhang, Liang; Yu, Lan; Ye, Wei; Liu, Zi-Yu; Ying, Qi-Kang; Wu, Xing-An; Xu, Zhi-Kai; Zhang, Fang-Lin (Frontiers in Cellular and Infection Microbiology, 2016)
A safe and effective Hantaan virus (HTNV) vaccine is highly desirable because HTNV causes an acute and often fatal disease (hemorrhagic fever with renal syndrome, HFRS). Since the immunity of the inactivated vaccine is weak and the safety is poor, HTNV virus-like particles (VLPs) offer an attractive and safe alternative. These particles lack the viral genome but are perceived by the immune system as virus particles. We hypothesized that adding immunostimulatory signals to VLPs would enhance their efﬁcacy. To accomplish this enhancement, we generated chimeric HTNV VLPs containing glycosylphosphatidylinositol (GPI)-anchored granulocyte macrophage colony-stimulating factor (GM-CSF) or CD40 ligand (CD40L) and investigated their biological activity in vitro. The immunization of mice with chimeric HTNV VLPs containing GM-CSF or CD40L induced stronger humoral immune responses and cellular immune responses compared to the HTNV VLPs and Chinese commercial inactivated hantavirus vaccine. Chimeric HTNV VLPs containing GM-CSF or CD40L also protected mice from an HTNV challenge. Altogether, our results suggest that anchoring immunostimulatory molecules into HTNV VLPs can be a potential approach for the control and prevention of HFRS.